Effect of using the flipped classroom learning strategy on the technical performance of 100 metres hurdles in female university students - Hameed, Nagham Hateem; Mashkoor, Najat Baqer (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
This research aimed to study the effect of using the flipped classroom learning strategy on the technical performance of 100 metres hurdles in female university students. The participants of this study were 24 female students of the second year of the College of Physical Education and Sports Sciences of the University of Baghdad, in the academic year 2020-2021. They were divided into two groups (experimental group and control group), each group containing 12 female students. The intervention program used the flipped classroom learning method in the experimental group, while the control group received the usual method of real-time explanation. The duration of the intervention program was 16 hours, with a total of 8 teaching units of 2 hours, implemented during a period of 4 weeks, at a rate of 2 educational units per week. The results of the experimental group were significantly better than the results of the control group (p<0.05), both in the technical performance of crossing the barrier and in the overall performance of 100m hurdles. In conclusion, the flipped classroom learning strategy significantly improved the technical performance of 100 metres hurdles in female university students.